Diffusive confinement of free radical intermediates in the OH radical oxidation of semisolid aerosols. Issue 9 (20th February 2017) - Wiegel, Aaron A.; Liu, Matthew J.; Hinsberg, William D.; Wilson, Kevin R.; Houle, Frances A.
Abstract : Reaction–diffusion simulations show that interfacial confinement of the reactions results in reactivity distinct from that in liquid hydrocarbon aerosol. Abstract : Multiphase chemical reactions (gas + solid/liquid) involve a complex interplay between bulk and interface chemistry, diffusion, evaporation, and condensation. Reactions of atmospheric aerosols are an important example of this type of chemistry: the rich array of particle phase states and multiphase transformation pathways produce diverse but poorly understood interactions between chemistry and transport. Their chemistry is of intrinsic interest because of their role in controlling climate. Their characteristics also make them useful models for the study of principles of reactivity of condensed materials under confined conditions. In previous work, we have reported a computational study of the oxidation chemistry of a liquid aliphatic aerosol. In this study, we extend the calculations to investigate nearly the same reactions at a semisolid gas–aerosol interface. A reaction–diffusion model for heterogeneous oxidation of triacontane by hydroxyl radicals (OH) is described, and its predictions are compared to measurements of aerosol size and composition, which evolve continuously during oxidation. These results are also explicitly compared to those obtained for the corresponding liquid system, squalane, to pinpoint salient elements controlling reactivity. The diffusive confinement of the free radical intermediates at the interface results in enhanced importance of a few specific chemical processes such as the involvement of aldehydes in fragmentation and evaporation, and a significant role of radical–radical reactions in product formation. The simulations show that under typical laboratory conditions semisolid aerosols have highly oxidized nanometer-scale interfaces that encapsulate an unreacted core and may confer distinct optical properties and enhanced hygroscopicity. This highly oxidized layer dynamically evolves with reaction, which we propose to result in plasticization. The validated model is used to predict chemistry under atmospheric conditions, where the OH radical concentration is much lower. The oxidation reactions are more strongly influenced by diffusion in the particle, resulting in a more liquid-like character.